Effect of behaviour change communication on dietary diversity among women of reproductive age from different socio-demographic background (cluster randomized controlled trial): a study protocol - Murarkar, Sujata; Gothankar, Jayashree; Doke , Prakash (International Journal Of Community Medicine And Public Health, 2025)
Background: Low diet quality of women of reproductive age group (WRA) will have an impact on their health due to deficiency of important micronutrients. Indicator of assessing quality of the diet is minimum dietary diversity for women (MDD-W). With this background present research will be conducted with the objective to compare the dietary diversity among women of reproductive age group who received intervention with among women who did not receive any intervention. Methods: Two-armed cluster randomized controlled trial will be conducted in urban slums and rural area of Pune district among women of reproductive age group. Estimated sample size will be of 325 participants in each arm. Data on dietary diversity will be collected and classified into ten food groups using 24-hour recall method. Behaviour change communication will be provided in two steps. Statistical analysis will be done using univariate and multivariate logistic regression, Chi-square test will be applied to test association between different socio- demographic variables and risk factors in the intervention and control arm. Conclusions: The study will contribute to the existing literature on dietary diversity among women of the 15-49 years’ age group of urban and rural parts of India, informing future research endeavors and policy initiatives. Trial registration number: CTRI/2025/02/080693.